Activity Based Cost Calculation Decision Making Tool - Yanti Octavia Selvianica Sigalingging; Gebriiella Sitorus; Thalia Sreshi Oxana Sidabalok; Willy Sangga Reja Galingging; Hamonangan Siallagan (Sean Institute, 2024)
This research aims to determine the relevant cost calculations carried out by companies in selling or further processing. Routine decision making generally occurs and is related to regular company operational activities. Relevant costs arise in situations where decision makers must choose between two or more options. Decision making will require information on relevant costs. When choosing between different alternatives, managers should concentrate only on costs and revenues that are among the decision systems.